TATA KELOLA PEMILU DALAM PEMENUHAN HAK-HAK PEMILIH PENYANDANG DISABILITAS: Kasus Pemilihan Gubernur dan Wakil Gubernur Provinsi Sumatera Barat Tahun 2015 di Kabupaten Padang Pariaman - Saputra, Ade Rio (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2018)
This study examines the electoral governance of disabled voters in the 2015 unlimited elections. This can be seen in the election of Governor and Vice Governor of West Sumatera Province in 2015 in Padang Pariaman Regency. The findings in this study are still not maximal electoral governance against the fulfillment of the rights of disability voters in Padang Pariaman regency in the election of Governor and Vice Governor of West Sumatra Province in 2015. Electoral governance consists of 3 levels of rule making, rule aplication and rule adjudication. Rule aplication is a level that is often ignored by the Electoral Management Body (EMB). This is evident from the socialization stage not implemented by the Padang Pariaman Regency Election Commission to the voters with disabilities. This has an impact on the low number of voters' participation in the 2015 election. The existing regulations are not in line with the technical implementation in the field. As the Electoral Management Body (EMB), the KPU must seriously manage and accommodate so as to ensure the political rights of every citizen who has the right to vote without exception including to the voters who have physical or mental limitations.